2019
DOI: 10.1108/lodj-01-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of servant leadership scale in Spanish higher education

Abstract: Purpose The purpose of this paper is twofold. First is the validation of a scale to measure the servant leadership of the university leaders. Second is to analyze how servant leadership affects the career satisfaction and life satisfaction of the academics. Design/methodology/approach Using a survey of 148 academics at universities located in Spain collected in May 2018, a couple of models were conducted using structural equation model techniques: a confirmatory factor analysis of second order in order to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 75 publications
(102 reference statements)
0
23
0
2
Order By: Relevance
“…Moreover, having disengaged workers with a low level of subjective wellbeing is a long-term survival risk for these institutions since religious organizations are usually less competitive on the market in terms of attracting and retaining talented workers [5,6]. According to Latif and Marimon [26], servant leadership and life satisfaction revealed a negative relationship in their recent study, in contrast with the theory [27,28]; therefore, they encouraged examining the relationship between them. Toward this end, this study showed a positive and significant correlation between servant leadership and satisfaction with life, confirming the previous studies of the theoretical framework and favoring the employment of this management style in institutions where the management of emotions attains a particular meaning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, having disengaged workers with a low level of subjective wellbeing is a long-term survival risk for these institutions since religious organizations are usually less competitive on the market in terms of attracting and retaining talented workers [5,6]. According to Latif and Marimon [26], servant leadership and life satisfaction revealed a negative relationship in their recent study, in contrast with the theory [27,28]; therefore, they encouraged examining the relationship between them. Toward this end, this study showed a positive and significant correlation between servant leadership and satisfaction with life, confirming the previous studies of the theoretical framework and favoring the employment of this management style in institutions where the management of emotions attains a particular meaning.…”
Section: Discussionmentioning
confidence: 99%
“…The scale of Reinke [4] is also similar in length to the shortest versions of these scales, which are SL-7 (global servant leadership scale) [34], SLBS-6 (servant leadership behavioral scale) [59], and even less than half the length of SLS (servant leadership survey; 18 items) [60]; these scales have not been selected due to being global measures rather than measuring multidimensional concepts. The scale in Reinke [4] is also shorter than the existing Spanish versions: 14 items [61], 30 items [62], and 36 items [26]. This fact raises the response rate, as larger scales usually decrease the respondent's attention by producing fatigue or boredom.…”
Section: Servant Leadership Scalementioning
confidence: 99%
See 1 more Smart Citation
“…El estilo de liderazgo servidor trae beneficios, no solo para el líder, sino para los seguidores también (Mostafa y El-Motalib, 2019). Existen pocas investigaciones sobre cómo los jóvenes ejecutivos perciben otros estilos de liderazgo, más allá de los estilos de liderazgo transaccional y transformacional; esto es cierto, particularmente, en aquellos relacionados con el intercambio de beneficios mutuos para líderes y empleados, como es el caso del estilo de liderazgo servidor (Latif y Marimon, 2019;Muenjohn et al, 2016). Los estudios respecto a liderazgo servidor han incluido organizaciones de bienes y servicios y son claros los beneficios que trae el practicar este estilo de liderazgo; sin embargo, a criterio propio de los autores a partir de sus experiencias personales, los estilos de liderazgo que más se estudian en las escuelas de negocio, centros de formación de líderes por excelencia suelen ser el estilo de liderazgo transformacional y el estilo de liderazgo transaccional y no se suele encontrar, en la malla curricular, temas relacionados con el liderazgo servidor.…”
Section: Introductionunclassified
“…Por fim, a sétima dimensão comum à liderança servidora refere-se ao comportamento ético. Nesse sentido, as ações são guiadas pelo relacionamento aberto e honesto com seguidores, cujo comportamento é centrado no funcionário (Latif & Marimon, 2019;Liden et al, 2008;van Dierendonck & Nuijten, 2011).…”
Section: Liderança Servidoraunclassified